Managing Muslim minorities in Russia - Akhmetova, Elmira (King Faisal Center for Research and Islamic Studies, 2018)
This paper examines the relations between the Kingdom of Saudi Arabia (Saudi Arabia) and the Russian Federation (RF) in the light of Muslim minority rights through analyzing the history of Islam in the Russian territory, with a focus on the rights of Muslims under the Tsarist rule since 1552 and during the existence of the Soviet Union. The first part of the paper suggests that, although Muslims are minority in modern Russia today, Islam established itself as an official religion in the Volga-Urals region and Caucasus during the early years of Islam. It also shows that the historical relations between Muslims and tsarist Russia were not always in conflict. The second part of the paper, which is based on Russian archival sources, presents a brief description of Soviet and Saudi Arabian diplomatic relations. The third part of the paper discusses the status of Islam and Muslims in modern Russia since the collapse of the Soviet Union and suggests that the tragedy of 9/11 and the US-led “Global War on Terror,” as its consequence resulted in religious discrimination and an anti-Islamic mood throughout the country. In 2002, the RF adopted a new law entitled, “On Fighting Extremist Activity.” This led to the decline of religious freedom, which directly harmed relations between Saudi Arabia and Russia. Donations coming from the Kingdom of Saudi Arabia through various channels were blocked, Saudi-funded institutions were banned as a part of the prevention of “Wahhabi” influences (which had been banned in Russia since 2002), and books (both original copies and translations) published in Saudi Arabia were banned as well. At the same time, the two governments continued working together on fighting against extremism, educational and cultural programs, and the development of Islamic banking in Russia. The last part of the essay includes some policy recommendations and concluding remarks.